2009
DOI: 10.1016/j.exer.2008.10.025
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of calcium homeostasis and signalling in the lens

Abstract: a b s t r a c tExcessive Ca 2þ can be detrimental to cells and raised levels of Ca 2þ in human lenses with cortical cataract have been found to play a major role in the opacification process. Ca 2þ homeostasis is therefore, recognised as having fundamental importance in lens pathophysiology. Furthermore, Ca 2þ plays a central role as a second messenger in cell signalling and mechanisms have evolved which give cells exquisite control over intracellular Ca 2þ ([Ca 2þ ] i ) via an array of specialised regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 84 publications
(100 reference statements)
1
75
0
3
Order By: Relevance
“…It restores the cytosolic Ca 2+ concentration to its low resting level (100 nM) and maintains a high (500 M) luminal ER Ca 2+ concentration [16]. Ultimately, the sodium/Ca 2+ -exchanger and plasma membrane Ca 2+ ATPase remove Ca 2+ from the cell [17] ( Fig. 1).…”
Section: Introductionmentioning
confidence: 96%
“…It restores the cytosolic Ca 2+ concentration to its low resting level (100 nM) and maintains a high (500 M) luminal ER Ca 2+ concentration [16]. Ultimately, the sodium/Ca 2+ -exchanger and plasma membrane Ca 2+ ATPase remove Ca 2+ from the cell [17] ( Fig. 1).…”
Section: Introductionmentioning
confidence: 96%
“…Calcium ions are of vital importance to many physiological processes and their concentrations are maintained within specific limits to ensure adequate homeostasis. 9 There is a wide consensus that the dis-regulation of the free intracellular calcium concentration ([Ca 2+ ] i ) and its pathological increase eventually lead to mechanisms causing some form of cell death. 10 The exact form/type of cell death is usually determined by the cell's physiological parameters accompanying the triggering events.…”
Section: Introductionmentioning
confidence: 99%
“…Walsh and Patterson (72) demonstrated that elevated [Ca2+]i in the lens of the frog eye has a central role in cataract formation and that calcium channel blockers, which of course block VGCC activation, can block cataract formation. In a recent review, it was shown that excessive [Ca2+]i in the lens of the human and mammalian eye plays a major role in the opacification process producing cataracts and that VGCCs can have a substantial role in this process (73). While these studies do not directly relate to microwave exposures, they clearly show that excessive [Ca2+]i in the lens of the eye has essential roles in cataract formation and that excessive VGCC activity causes cataract formation in experimental animals.…”
Section: Cataract Formation As Claimed Effects Of Microwave-caused Hementioning
confidence: 99%